The chronic ills of multimorbidity : a cross-sectional examination of the prevalence, patterns and factors associated with multimorbidity in the Irish population aged 50 years and over and its corresponding impact on health and social care utilisation - McDaid, Olga (Trinity College (Dublin, Ireland). School of Medicine. Centre of Health Policy and Management, 2013)
Multimorbidity predicts many adverse health outcomes, placing a heavy burden on the individual as well as population health. It has clear implications for current healthcare provision and with the projected ageing of the Irish population presents substantial challenges for future healthcare policy and planning. Population level evidence on multimorbidity is, however, limited. The factors driving multimorbidity prevalence are poorly understood and appropriate responses have yet to be integrated into population health planning and service delivery. The overall aim of this thesis was to gain a greater understanding of the prevalence, patterns and factors associated with multimorbidity at a population level in Ireland, as well as the corresponding impact of multimorbidity on health and social care utilisation. Three separate but related empirical studies were conducted based on the following central objectives: -- 1. To estimate the prevalence and non-random patterning of multimorbidity in the community-dwelling population aged 50 years and over in Ireland. -- 2. To examine the factors associated with multimorbidity in mid to late life in an Irish context. -- 3. To determine the impact of multimorbidity on health and social care utilisation and quality of care in Ireland. Conceptual issues of multimorbidity definition and measurement were considered in this thesis to contextualise multimorbidity within population health and inform a framework for evaluating multimorbidity in community-dwelling populations.
Keywords: Public Health and Primary Care, Ph.D.; Ph.D. Trinity College Dublin